2001
DOI: 10.1182/blood.v98.3.771
|View full text |Cite
|
Sign up to set email alerts
|

Identifying intercellular signaling genes expressed in malignant plasma cells by using complementary DNA arrays

Abstract: In multiple myeloma (MM), the growth of primary plasma cells depends not only on interleukin-6 (IL-6), but also on additional unidentified signals delivered by the bone marrow environment. Using Atlas complementary DNA (cDNA) arrays comprising 268 genes coding for intercellular signaling molecules, this study identified genes that are overexpressed in myeloma cells compared to autologous B-lymphoblastoid cell lines. These genes encode the oncogenic Tyro3 tyrosine kinase receptor, the heparin-binding epidermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
97
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(102 citation statements)
references
References 67 publications
5
97
0
Order By: Relevance
“…Previous reports have demonstrated that CCR2 is expressed on normal, mature B cells (Frade et al, 1997). Very recently, transcripts for this receptor were also identified in myeloma plasma cells, as demonstrated by cDNA arrays (De Vos et al, 2001). Our data show that CCR2 is also expressed in both, normal and malignant plasma cells, at the protein level.…”
Section: Discussionsupporting
confidence: 71%
“…Previous reports have demonstrated that CCR2 is expressed on normal, mature B cells (Frade et al, 1997). Very recently, transcripts for this receptor were also identified in myeloma plasma cells, as demonstrated by cDNA arrays (De Vos et al, 2001). Our data show that CCR2 is also expressed in both, normal and malignant plasma cells, at the protein level.…”
Section: Discussionsupporting
confidence: 71%
“…In the current experiments, cells were cultured at a low concentration to limit the biological activity of autocrine loops involving EGF-ligands. Indeed, we have previously shown that autocrine HB-EGF contributes to the IL-6-induced growth of some IL-6-dependent HMCLs cultured at a high cell density (De Vos et al, 2001;Wang et al, 2002;Mahtouk et al, 2004). Compiling our previous data about ErbB expression in HMCLs with those of EGF-ligand expression, we provide here a comprehensive description of autocrine loops in HMCLs.…”
Section: Discussionmentioning
confidence: 66%
“…Growth factors (1 mg) were added at the beginning of the culture in six culture wells per group. At the end of the culture, cells were pulsed with tritiated thymidine (Amersham Pharmacia Biotech, Orsay, France) for 12 h, harvested and counted as reported previously (De Vos et al, 2001). …”
Section: Myeloma Cell Proliferation Assaymentioning
confidence: 99%
“…Proliferation of HMCLs was investigated as previously published (De Vos et al, 2001). Cells were cultured in RPMI-1640 containing 10% fetal calf serum and graded concentrations (0.00128, 0.0064, 0.032, 0.16, 0.8 and 4 mg/ml) of BMP6.…”
Section: Measurement Of Proliferation By 3 H-thymidinementioning
confidence: 99%